Once upon a crime - Buckley, Michael; Ferguson, Peter, 1968- (New York : Amulet Books, 2007)
When the fairy-tale detectives rush to New York City hoping to find an Everafter who can cure Puck, they trigger a chain of events that includes a murder mystery, and learn many new things about their mother who, along with their father, is still in an enchanted sleep.
Keywords: Characters and characteristics in literature -- Juvenile fiction; Sisters -- Juvenile fiction; Grandmothers -- Juvenile fiction; Characters in literature -- Fiction; Sisters -- Fiction; Grandmothers -- Fiction; Mystery and detective stories; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction; Mystery fiction